2021
DOI: 10.3390/genes12101470
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Lysine Deacetylases in Virulence, Resistance, and Production of Small Bioactive Compounds

Abstract: The growing number of immunocompromised patients begs for efficient therapy strategies against invasive fungal infections. As conventional antifungal treatment is increasingly hampered by resistance to commonly used antifungals, development of novel therapy regimens is required. On the other hand, numerous fungal species are industrially exploited as cell factories of enzymes and chemicals or as producers of medically relevant pharmaceuticals. Consequently, there is immense interest in tapping the almost inexh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 174 publications
(307 reference statements)
1
4
0
Order By: Relevance
“…The mycoparasitic overgrowth of R. solani by the ∆hda1 mutant was severely delayed, whereas B. cinerea could not be completely overgrown. To date, the majority of studies reported on a critical impact of the class I HDAC Hos2 on virulence or pathogenicity in other fungi ( 10 , 11 ), and, consistent with our findings, the class II HDAC Hda1 was also described as virulence determinant in some species. In Cryptococcus neoformans , Hda1 is a central mediator of virulence ( 49 ); in the plant pathogen M. oryzae , hda1 gene deletion caused a 60% reduction of lesions ( 50 ); and in F. fujikuroi , a 25% reduction of internode elongation in the host plant Oryza sativa was reported ( 21 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mycoparasitic overgrowth of R. solani by the ∆hda1 mutant was severely delayed, whereas B. cinerea could not be completely overgrown. To date, the majority of studies reported on a critical impact of the class I HDAC Hos2 on virulence or pathogenicity in other fungi ( 10 , 11 ), and, consistent with our findings, the class II HDAC Hda1 was also described as virulence determinant in some species. In Cryptococcus neoformans , Hda1 is a central mediator of virulence ( 49 ); in the plant pathogen M. oryzae , hda1 gene deletion caused a 60% reduction of lesions ( 50 ); and in F. fujikuroi , a 25% reduction of internode elongation in the host plant Oryza sativa was reported ( 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…“Classical”—Zn 2+ ion binding—fungal lysine deacetylases can be assigned to class I (Rpd3 family comprising the enzymes Rpd3 and Hos2) and class II (Hda1 family comprising the enzymes Hda1 and Hos3) HDACs, based on their sequence similarity to the respective Saccharomyces cerevisiae orthologues ( 11 15 ). Functional characterization of the class I HDAC Hda-2 in T. atroviride —the orthologue of S. cerevisiae Hos2—was described to regulate growth, conidiation, blue light perception, and oxidative stress response ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histone deacetylation is the most widely studied among fungal epigenetic modifications ( Bauer and Graessle, 2021 ). HDACs are important in eukaryotic cells which play an essential role in gene expression, transcription and post-transcriptional protein modification by reducing the acetylation level of histones.…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…When used in combination with FLC, HDAC inhibitors 1 , TSA, and MGCD290 significantly improved the sensitivity of FLC against resistant C. albicans isolates by reducing the expression of ERG3, ERG11 (encoding azole targets), and CDR/MDR1 (encoding multidrug transporters) genes. …”
Section: Introductionmentioning
confidence: 99%